Research on Parkinson’s disease immunotherapy: a bibliometric analysis via multiple databases - Fei, Xinxing; Wang, Shiqi; Song, Jiayi; Cao, Caihong; Gao, Yaqian; Hu, Yue (Frontiers in Immunology, 2025)
BackgroundParkinson’s disease (PD) is a neurodegenerative disorder involving degeneration of dopaminergic neurons in the substantia nigra, abnormal aggregation of α-synuclein, and neuroinflammatory response. Although research on PD immunotherapy is advancing rapidly, bibliometric analysis in this field remains underdeveloped.MethodsLiterature related to “Parkinson’s disease” and “immunotherapy” from the Web of Science Core Collection and Scopus was used for data merging and bibliometric analysis via Bibliometrix. The characteristics of the relevant clinical trials in this field retrieved from the PubMed database were summarized, and the study protocols were traced back through the trials registry website.ResultsAfter merging the two databases, a total of 890 documents from 488 sources were covered. A total of 3,804 researchers from 1,483 institutions in 63 countries published research in this field. Authors, institutions, and countries/regions were classified into 5, 12, and 13 clusters, respectively. Keywords such as “Parkinson’s disease”, “immunotherapy”, and “alpha-synuclein” were frequently used. The maps of keyword co-occurrence and clusters revealed the generation of two clusters. A total of 8 clinical trials were searched and included. These trials focused on active immunotherapy and targeted antibodies, involving both healthy volunteers and patients with PD.ConclusionsThe field of PD immunotherapy has vigorous development potential. The current research focus in this field is concentrated on analyzing pathological mechanisms and innovating treatment strategies. Precise immunological intervention techniques are frontiers in this field. In the future, large-scale randomized controlled trials should be conducted to enhance the clinical translation efficiency of immunotherapy.